Green hydrogen: The only oxygen and water balanced fuel. Issue 3 (March 2021) - Newborough, Marcus; Cooley, Graham
Abstract : The use of any fuel depletes the oxygen content of the atmosphere, with one exception: hydrogen produced from water. Water electrolysis liberates oxygen from water in the precise stoichiometric ratio required to oxidise (and hence release energy from) the co-produced hydrogen. As a commercial fuel production process, electrolysis is unique in providing the oxidant as well as the fuel; electrolytic oxygen can thereby replenish the consumption of atmospheric oxygen due to hydrogen use. Furthermore, the amount of water consumed during electrolysis is reproduced when the hydrogen is oxidised. So the use of electrolysers and electrolytic hydrogen does not affect global oxygen and water resources: 'green' hydrogen may thus be described as the only oxygen and water balanced fuel. Conversely, the use of hydrogen derived from fossil fuels (with or without carbon capture and storage, CCS) depletes the oxygen resource and increases water vapour emissions to the atmosphere, which enhances the rate of global warming. Therefore, a worldwide multi-TW deployment of electrolysers could provide very substantial amounts of hydrogen for the energy system, and oxygen for the global ecosystem. This should be done in combination with other measures for combatting oxygen depletion (such as reducing combustion, increasing forestation, and reducing nutrient inputs to the ocean from sewage and agriculture). In this way the long-term objective should be to stabilise, or even increase slightly, the concentrations of atmospheric and aquatic oxygen, and possibly speed up the decay of atmospheric methane. Clearly the production-and-use of hydrogen derived from fossil fuels contravenes this objective, and should cease without delay.